2019
DOI: 10.1080/21650020.2019.1604155
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of attitudes to autonomous vehicles

Abstract: For the benefits of autonomous vehicles (AVs) to be optimized, the fleet conversion process needs to be efficient and timely. This study explored public attitudes to AVs to inform strategies to increase receptivity to the wide-scale use of AVs. A national online survey was administered to a sample of 1,624 Australians aged 16+ years. The survey featured open-ended questions that scoped respondents' perceptions of AVs. A grounded, thematic analysis identified two primary dimensions in the data: response valence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…According to observer's (agent's) perspective, people want to know how communal an AV is (how agentic an AV is). These results supported H1, and are consistent with a previous study [16] which reported that people expect tangible information about control issues of AVs and their safety. These results are also coherent with the notion that the communion and agency are distinctly expressed in natural language [79,132].…”
Section: Theoretical Contributionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to observer's (agent's) perspective, people want to know how communal an AV is (how agentic an AV is). These results supported H1, and are consistent with a previous study [16] which reported that people expect tangible information about control issues of AVs and their safety. These results are also coherent with the notion that the communion and agency are distinctly expressed in natural language [79,132].…”
Section: Theoretical Contributionsupporting
confidence: 92%
“…Finally, AVs enable comfortable traveling for people unfit for independent driving, e.g., the elderly and people with disabilities [ 15 ]. However, introduction of AVs is connected with multiple challenges such as safety, legal liability, ethical questions and regulatory issues, which result in consumers’ fear towards this tech [ 16 18 ]. AVs also are a challenge to the traditional role of drivers and driving pleasure [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on attitudes and trust towards autonomous technology utilize self-reporting questionnaires (e.g. [17,18]). This approach has several limitations: rst, the vast majority of participants respond without any prior experience as a passenger or driver of self-driving vehicles.…”
Section: Introductionmentioning
confidence: 99%
“…Epochs with a signal range exceeding 100 µV (typically due to movement or blink artefacts) were excluded from further analysis. Power spectral densities (PSD) were calculated to alpha (8-12 Hz), beta(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and gamma(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) band ranges utilizing the Welch method. For each epoch, an index for valence (affectivity) and arousal were computed.…”
mentioning
confidence: 99%
“…The transport sector is in a phase of rapid change due to the emergence of autonomous vehicles (AVs) ( Crayton and Meier, 2017 ; Fagnant and Kockelman, 2015 ). Numerous AV trials are in progress at sites all around the world, and anticipated user response has been the subject of an increasing number of studies (e.g., Kyriakidis et al, 2015 ; Bansal and Kockelman, 2017 ; Pettigrew et al, 2018 , Pettigrew et al, 2019b ). AVs are projected to have a significant impact on the future of urban mobility, and it is widely expected that they will have the potential to offer door-to-door solutions, which could be especially beneficial for those with mobility limitations ( Kovacs et al, 2020 ; Pettigrew et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%